Maternal obesity-induced decreases in plasma, hepatic and uterine polyunsaturated fatty acids during labour is reversed through improved nutrition at conception - Muir, Ronan Davidson; Liu, Ge; Khan, Raheela; Shmygol, Anatoly; Quenby, Siobhan; Gibson, Robert Alan; Muhlhausler, Beverly; Elmes, Matthew (Nature Publishing Group, 2018)
Maternal obesity is associated with prolonged and dysfunctional labour, potentially through decreased synthesis of prostaglandins that stimulate myometrial contractions. We assessed the impact of maternal obesity on concentrations of precursor fatty acids (FA) for prostaglandin synthesis and whether any changes could be reversed by improved nutrition post-conception. Wistar rats were fed control (CON) or High-Fat, High-cholesterol (HFHC) diets 6 weeks before mating. At conception half the dams switched diets providing 4 dietary groups: (1) CON, (2) HFHC, (3) CON-HFHC or (4) HFHC-CON. During parturition rats were euthanized and FA composition of plasma, liver and uterus determined. Visceral fat was doubled in rats exposed to the HFHC diet prior to and/or during pregnancy compared to CON. HFHC diet increased MUFAs but decreased omega-3 and omega-6 PUFAs in plasma and liver. Uterine omega-3 FA concentrations were halved in HFHC versus CON rats, but all other FAs were similar. Switching from HFHC to CON diet at conception restored all FA profles to those seen in CON rats. The increased MUFA and decreased PUFA concentrations in obese HFHC dams may contribute to aberrant prostaglandin synthesis and dysfunctional myometrial activity and it may be possible to reverse these changes, and potentially improve labour outcomes, by improving nutrition at conception.